Non-Markovian dynamics of quantum systems coupled with several mixed fermionic-bosonic heat baths; Physical Review E; Vol. 101, iss. 6 - Hovhannisyan A. A. Arshak; Sargsyan V. V. Vazgen Valerikovich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lacroix D. (2021, 2021)
Title screen